Effects of Long-Term Low-Protein Diets Supplemented with Sodium Dichloroacetate and Glucose on Metabolic Biomarkers and Intestinal Microbiota of Finishing Pigs - Yetong Xu; Huiyuan Chen; Ke Wan; Zhiru Tang; Weizhong Sun; Liuting Wu; Zhongxiang Ren; Qi Ding; Kaiyang Liang; Zhihong Sun (Animals, 2022)
The objective of this study was to evaluate the effects of low-protein (LP) diets supplemented with sodium dichloroacetate (DCA) and glucose (GLUC) on metabolic markers and intestinal microbiota of finishing pigs. A total of 80 crossbred growing barrows were allocated randomly to one of the five treatments, including the normal protein level diet (CON), the LP diets, LP with 120 mg/kg DCA (LP + DCA) or 1.8% glucose (LP + GLUC), and LP with 120 mg/kg DCA and 1.8% glucose (LP + DCA + GLUC). The LP diet increased the plasma HDL, triglyceride, and cholesterol concentrations and reduced the bile acid, urea nitrogen, albumin, and total protein concentrations compared to the CON diet (p < 0.05). The LP + DCA + GLUC diet reduced the plasma VLDL, triglyceride, and cholesterol concentrations and increased the bile acid concentration compared with the LP diet (p < 0.05). Pigs fed the LP + DCA and LP + GLUC diets showed reduced 3-Hydroxy-3-Methylglutaryl-CoA Reductase content and increased Cytochrome P450 Family 7 Subfamily A Member 1 activity of liver compared that of the CON diet (p < 0.05). Moreover, the LP diets with or without DCA and GLUC supplementation increased the relative abundance of colonic microbiota related to carbohydrate fermentation in finishing pigs. In conclusion, 120 mg/kg DCA or 1.8% GLUC supplementation in an LP diet modulated the hepatic lipid metabolism of pigs, while the DCA along with GLUC supplementation likely improved the lipid metabolism by stimulating bile acid secretion.